PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Samsuri . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this article is to explain about the influence of situational leadership style and work discipline to work achievement of employee in East Kutai. The result shows that leadership style and work discipline have strong influence to increasemen of work achievement.